Association of Serum Osteoprotegerin Level With Myocardial Injury and Cardiovascular Calcification in Chronic Kidney Disease Patients - Okasha, Kamal M.; Aboufreikha, Mohamed Hussein; Elrefaey, Waleed; Ashmawy, Medhat M.; Mourad, Heba; Elsebaey, Mohamed A.; Elnaggar, Mohammed H.; Mashaal, Raghda Gabr; Metwally, Sama; Mashal, Shaimaa Samir Amin; Shalaby, Neveen A.; Elhoseny, Shireen Ali; et al. (Frontiers in Medicine, 2022)
Background: Chronic kidney disease (CKD) has emerged as a significant independent risk factor for cardiovascular disease (CVD) in CKD patients. Cardiovascular calcification (CVC) is an active process involving a complex interaction of inducers and inhibitors. High sensitivity cardiac troponin T (hs-cTnT) assay detects troponin T with higher sensitivity and precision at an earlier point of time than the conventional assays, and is associated with poor outcomes. Serum Osteoprotegerin (OPG) is classed as an inhibitory factor for CVC. It is involved in the pathological processes of vascular damage and linked to the excess cardiovascular morbidity in CKD. The aim of the present study was to evaluate the extent of CVC and serum hs-cTnT level, and their association with serum OPG level in patients with CKD stages 3-5. Methods: 90 CKD patients were enrolled in this study, and they were divided into 2 groups: group (1) included 45 non-dialysis-dependent CKD patients (stages 3-5) and group (2) included 45 chronic hemodialysis patients. Each group further subdivided according to the presence of CVC into subgroup A and B. Vascular calcifications were assessed by lateral lumbar, pelvis and hands X-ray radiographs. Valvular calcification was assessed by echocardiography. Serum cardiac troponin T was measured by high sensitivity assay and serum OPG was measured by ELISA. Results: CVC distribution was 22.2% in group (1) and 33.3% in group (2). Serum OPG and hs-cTnT in calcification groups (1A and 2A) were significantly higher than non-calcification groups (1B and 2B) (P < 0.001). OPG correlated positively with hs-cTnT (rs = 0.72, P < 0.001). CVC correlated positively with OPG, hs-cTnT and phosphorus. OPG and phosphorus were significant independent predictors of CVC at cut-off values ≥ 4.6 ng/L and ≥ 6.95 mg/dl, respectively (P < 0.001). Serum phosphorus and creatinine were independent predictors of OPG (P < 0.001 and = 0.048, respectively). Conclusion: Osteoprotegerin is strongly associated with CVC and hs-cTnT. In addition, there is a positive association between CVC and hs-cTnT. This suggests a role for OPG in the pathogenesis and risk stratification of CVC and myocardial injury in CKD patients with a potential role as a therapeutic target.